Pengaruh Pendekatan STEM-SDGs terhadap Keterampilan Saintifik Siswa dan Hasil Belajar Materi Sistem Ekskresi di SMA Islam Samarinda - Huda, Nafisahtul; Nasution, Ruqoyyah; Rambitan, Vandalita Maria Magdalena; Masitah, Masitah; Kurniawati, Zenia Lutfi; Makkadafi, Suparno Putera (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to determine the influence of the STEM-SDGs approach on improving scientific skills and student learning outcomes on Excretory System material at SMA Islam Samarinda. This study uses a quasi experiment method with a non-equivalent control group design. The research sample was selected through a purposive sampling technique consisting of two groups, namely the experimental class of 26 students and the control class of 26 students. Data analysis was carried out using an independent sample t-test. The results of the study show that the STEM-SDGs approach has a significant effect on improving students' scientific skills, especially in the aspects of observing, reasoning, and communicating, as well as on learning outcomes shown through improving post-test scores. The engineering aspect is the most influential component, because it trains students to design and create projects based on the use of used goods according to the SDGs. Thus, it can be concluded that the STEM-SDGs approach is effective in improving students' scientific skills and learning outcomes through integrative and contextual project-based learning.